HYBRID MODULE EFFECT ON STUDENTS' LEARNING MOTIVATION AND ACHIEVEMENT IN ENGLISH FOR FRONT OFFICE COURSE - Wedhanti, Nyoman Karina; Yuliasri, Issy; Ana, I Ketut Trika Adi (Language Circle: Journal of Language and Literature, 2023)
This study aimed at identifying the effect of the hybrid module on students' learning motivation and achievement in the English for Front Office Course. The hybrid module, in this study, is a printed module that provides online videos and quizzes that can be accessed using smartphones by scanning the QR codes on the printed module. This study was conducted at Vidya Wisata Senior High School. The researchers selected 37 students who took the English for Front Office course as the study samples. The data were collected using questionnaires and tests. The researchers used the questionnaires to collect data on students' learning motivation and the tests to measure students' achievement in the English for Front Office Course. Those questionnaires and tests were given to the students before and after they were taught using the hybrid module. The data from the questionnaire and tests were analyzed quantitatively using paired t-tests. The study results show that the hybrid module significantly affects the student's motivation and achievement in English for Front Office Course. This study also found that the hybrid module has a large effect on students' learning motivation and achievement. Detailed findings with a discussion based on the related theories and empirical reviews are provided in this article.